Early medieval reliance on the land and the local: An integrated multi-isotope study (87Sr/86Sr, δ18O, δ13C, δ15N) of diet and migration in Co. Meath, Ireland. (October 2018) - Ryan, Saskia E.; Reynard, Linda M.; Crowley, Quentin G.; Snoeck, Christophe; Tuross, Noreen
Abstract: Three early medieval Irish communities within a 30-km radius in Co. Meath, Ireland, have been examined using multiple isotopes ( 87 Sr/ 86 Sr, δ 18 O, δ 13 C, δ 15 N) to elucidate human and domesticated animal subsistence and provenance. Existing 87 Sr/ 86 Sr data from geochemical mapping of contemporary soils, plants and streamwater were compared to human and animal tooth enamel 87 Sr/ 86 Sr to assess potential past human migration, in combination with δ 18 O from bone collagen. Oxygen isotope (δ 18 O) values of human bone collagen are notably invariable, 10.0 ± 0.6‰ (n = 36), for the three archaeological sites: Collierstown, Johnstown and Raystown. Fauna (sheep, pigs, cats and a dog) δ 18 Ocollagen from Raystown are distinctly grouped between and among certain species, the first instance to our knowledge of such a result. The aggregate faunal data demonstrate that δ 18 Ocollagen values of faunal remains should not be used to infer local δ 18 O ranges for humans. Nitrogen isotope (δ 15 N) values for both domesticated animal (9.8 ± 1.7‰) and adult human (12.0 ± 0.8‰) bone collagen are tightly constrained suggesting a similar source of protein in the diet of humans. A mean carbon isotope (δ 13 C) value of −21.0 ± 0.4‰ for adult humans indicates overwhelming terrestrial sources of foodstuffs. Strontium isotope ratios ( 87 Sr/ 86 Sr) from human dental enamel range from 0.7085-0.7110 (n = 25). Two individuals (R841 and R854), both from Raystown, are statistical outliers based on their 87 Sr/ 86 Sr and δ 13 C values and are likely migrants to the locality where they were buried. We note that one of these putative migrants met a particularly violent end. Highlights: Isotopes ( 87 Sr/ 86 Sr, δ 18 O, δ 13 C, δ 15 N) of three early medieval Irish sites are presented. Two individuals are outliers based on 87 Sr/ 86 Sr and δ 13 C and are likely migrants. Oxygen isotope (δ 18 O) values of human bone collagen are invariable, 10.0 ± 0.6‰. Fauna (sheep, pigs, cats and a dog) δ 18 Ocollagen group between and among species.